PROBLEMS OF REALIZATION OF THE PROSECUTOR POWERS IN CARRYING OUT SUPERVISION OVER THE IMPLEMENTATION OF LAWS - Elnara Islamova (Krymskij Naučnyj Vestnik, 2016)
The article considers the problems of realization of the Prosecutor powers in carrying out supervision over the implementation of laws. Based on the analysis of Russian legislation and the legislation of the CIS measures to improve the regulation of Prosecutor powers are proposed.